If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5x + -6) = 2x + -12 Reorder the terms: -2(-6 + 5x) = 2x + -12 (-6 * -2 + 5x * -2) = 2x + -12 (12 + -10x) = 2x + -12 Reorder the terms: 12 + -10x = -12 + 2x Solving 12 + -10x = -12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -10x + -2x = -12 + 2x + -2x Combine like terms: -10x + -2x = -12x 12 + -12x = -12 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -12x = -12 + 0 12 + -12x = -12 Add '-12' to each side of the equation. 12 + -12 + -12x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -12x = -12 + -12 -12x = -12 + -12 Combine like terms: -12 + -12 = -24 -12x = -24 Divide each side by '-12'. x = 2 Simplifying x = 2
| 8x-0.1=0.5-0.2(4-5x) | | 13(t-2)+5t=6(3t+4)-8 | | (3x-5)-(-4x+1)= | | 6-(3-c)= | | 15=5-5x | | 3x^2+2x+120=0 | | 5x+(-x)+(-1)=5-2x | | -70=-5(1-2p)-5 | | -70=-5(1-2p)-5 | | 2x-5(x-5)=-9+3x+16 | | 16+x=-x | | 30=1.24c | | 16x+4y=180 | | -8x-0.1=0.5-0.2(4-5x) | | 30+12+2x+10=180 | | 4+3f=5+4f | | 2(w-4)=20-2w-12 | | x+4.23=-30 | | 2x-xy+2y-y^2=0 | | 32+2n+32=126 | | -30+5b=-6(b-6) | | (2m+7)-(-3+4m)= | | 4(x+4)=8x+32 | | 2(A-30)+B=180 | | 3x^3-7x^2+14x-4=0 | | (60+5)-(2-3d)= | | 135+3x=30x | | cos(sinx)=1 | | 6s+4-2s=24 | | -17-5(x+3)=3x | | x^2-22x+.85=0 | | 32+2n=126 |